A VHF Band Small CRLH Antenna Using Double-Sided Meander Lines - Lee, Soyeong; Park, Yong Bae (Applied Sciences (Switzerland), 2022)
In this paper, a miniaturized very-high frequency (VHF) band antenna using both top and bottom meander lines is proposed. To design a compact size antenna in the VHF band, a Composite Right/Left-Handed (CRLH) transmission line is applied to antenna structure; additionally, both top and bottom meander lines were used to achieve a greater inductance. The CRLH transmission line unit cell operates at 88 MHz, and the fabricated antenna is designed by arranging 7-unit cells. The overall size of the proposed antenna is 0.087λ × 0.02λ × 0.0003λ at the lowest operating frequency, and the antenna operates at 84 MHz. The VSWR 3.5:1 reference operating bandwidth of the antenna is 2%. The received power of the proposed CRLH antenna was measured to verify the antenna performance.
Keywords: composite right/left-handed transmission lines; meander lines; military antenna; VHF (very high-frequency)